Quality of life in patients with multiple sclerosis - Snarska, Katarzyna; Karwowska, Milena; Kapica-Topczewska, Katarzyna; Drozdowski, Wiesław; Bachórzewska-Gajewska, Hanna (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. Multiple sclerosis is a chronic autoimmune disease of the central nervous system. It changes patients’ lives and their families, makes tough choices, loses hope and desire to fight against the disease, reduces the quality of life. Aim. The aim of the study was assessment of quality of life of patients with multiple sclerosis and the factors which can influence this assessment. Material and methods. The study was conducted using a questionnaire, designed for this study and the standard WHOQOL-BREF and Extended Disability Status Scale (EDSS), among 100 patients with multiple sclerosis. Results. In the study group was 32 men (32%) and 68 women (68%). The mean age of patients was 10.3 ± 41.9 years. The mean disease duration was 11.1 ± 8,9lat. The mean EDSS was 2.7 ± 2.0. Overall quality of life and general health assessment in the questionnaire WHOQOL was 3.4 ± 0.9, and general health assessment was equal to 2.9 ± 0.8. Conclusions. Malfunction of patients increased with age of the patient, duration of illness, number of views, and decreased as a result of hospitalization and the appropriate treatment and affect the operation in all areas. The decrease in the overall quality of life in patients with multiple sclerosis affect of illness, number of throws and the scale of motor failure and did not affect her diagnosis, the treatment and age of onset.